2015
DOI: 10.1099/mic.0.000155
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of an international Pseudomonas aeruginosa reference panel: strains of cystic fibrosis (CF) origin show less in vivo virulence than non-CF strains

Abstract: Pseudomonas aeruginosa causes chronic lung infections in people with cystic fibrosis (CF) and acute opportunistic infections in people without CF. Forty-two P. aeruginosa strains from a range of clinical and environmental sources were collated into a single reference strain panel to harmonise research on this diverse opportunistic pathogen. To facilitate further harmonized and comparable research on P. aeruginosa, we characterized the panel strains for growth rates, motility, virulence in the Galleria mellonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 60 publications
5
72
0
Order By: Relevance
“…This variability in MICs could be considered somewhat unexpected for what is essentially a novel antibiotic compound being administered to a naive population. However, recent studies have reported significant phenotypic and genotypic diversity within clinical populations, suggesting that adaptation to environmental or host-related factors may be widespread (46)(47)(48). While the mechanism of action of statin antimicrobial and antivirulence activity remains to be elucidated, some reports suggest the involvement of isoprenoids and membrane integrity (49).…”
Section: Effects Of Statins On In Vitro Bacterial Growthmentioning
confidence: 99%
“…This variability in MICs could be considered somewhat unexpected for what is essentially a novel antibiotic compound being administered to a naive population. However, recent studies have reported significant phenotypic and genotypic diversity within clinical populations, suggesting that adaptation to environmental or host-related factors may be widespread (46)(47)(48). While the mechanism of action of statin antimicrobial and antivirulence activity remains to be elucidated, some reports suggest the involvement of isoprenoids and membrane integrity (49).…”
Section: Effects Of Statins On In Vitro Bacterial Growthmentioning
confidence: 99%
“…The lytic activity of PA5oct was examined on two independent P. aeruginosa panels. First, on the COST international reference panel of 43 clinical P. aeruginosa (Cullen et al , 2015). On that collection, phage PA5oct infects 24% of the isolates, a rate that is more limited when compared to representatives of the Luz7virus LUZ7 (42%), Phikmvvirus group (LUZ19 44%), Pbunavirus group (LBL3 40%, KT28 28%, KTN6 42%) and Phikzvirus group (phiKZ 47%, KTN4 33%).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed an increase in CFTR mRNA levels in treated tissues. Loss of CFTR function leads to the development of chronic bacterial lung infections (26, 27). In CF pigs, loss of CFTR-mediated bicarbonate transport leads to acidic airways and impaired bacterial killing (16).…”
Section: Discussionmentioning
confidence: 99%